When the World Spoke French - Fumaroli, Marc; Howard, Richard (New York New York Review Books, 2001)
During the eighteenth century, from the death of Louis XIV until the Revolution, French culture set the standard for all of Europe. In Sweden, Austria, Italy, Spain, England, Russia, and Germany, among kings and queens, diplomats, military leaders, writers, aristocrats, and artists, French was the universal language of politics and intellectual life. In When the World Spoke French, Marc Fumaroli presents a gallery of portraits of Europeans and Americans who conversed and corresponded in French, along with excerpts from their letters or other writings. These men and women, despite their differences, were all irresistibly attracted to the ideal of human happiness inspired by the Enlightenment, whose capital was Paris and whose king was Voltaire. Whether they were in Paris or far away, speaking French connected them in spirit with all those who desired to emulate Parisian tastes, style of life, and social pleasures. Their stories are testaments to the appeal of that famous "sweetness of life" nourished by France and its language.
Keywords: 18th Century (1701-1800); French; Cuckoo; Europe